The Impact of Entrepreneurship Intervention Scheme on Risk of Exposure to Poverty in a Developing Economy. - Uduakobong Inyang (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study examined the impact of a financial support scheme targeted at existing micro-entrepreneurs on the risk of exposure to poverty. Data was collected from a population of micro-entrepreneurs in Akwa Ibom State that received financial support from Right Honorable Aniekan Bassey Youth Entrepreneurship Support Scheme, RHAB –YESS, for the period 2020 and 2022 with the use of a structured questionnaire. Logistic regression was used in the data analysis. The results indicate a reducing effect of access to financial support on risk of exposure to poverty among the entrepreneurs. The finding suggests targeted financial support of existing entrepreneurs as a veritable strategy for poverty alleviation.